2013
DOI: 10.1016/j.domaniend.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between melatonin and follicle-stimulating hormone promotes in vitro development of caprine preantral follicles

Abstract: The aim of this study was to investigate the effects of melatonin and follicle-stimulating hormone (FSH) on the in vitro culture of goat preantral follicles. Ovarian fragments were cultured for 7 d in α-minimum essential medium (α-MEM(+)) containing melatonin (100, 250, 500, or 1,000 pM), FSH (50 ng/mL), or a combination of the 2 hormones and further analyzed by histology and transmission electron and fluorescent microscopy. The results showed that after 7 d of culture, tissues cultured in α-MEM(+) alone or su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…The decrease in the thickness of theca interna supports the hypothesis of reduced androgen biosynthesis by the ovary. Melatonin has been shown to stimulate folliculogenesis in primordial follicles when co‐incubated with FSH [43]. As a result, there was an increase in percentage of ovulated follicles in melatonin groups when compared with positive control.…”
Section: Discussionmentioning
confidence: 97%
“…The decrease in the thickness of theca interna supports the hypothesis of reduced androgen biosynthesis by the ovary. Melatonin has been shown to stimulate folliculogenesis in primordial follicles when co‐incubated with FSH [43]. As a result, there was an increase in percentage of ovulated follicles in melatonin groups when compared with positive control.…”
Section: Discussionmentioning
confidence: 97%
“…When cultured caprine ovarian fragments containing primordial follicles were incubated in medium containing both melatonin (concentrations ranging from 100 pM to 1 nM) and follicle stimulating hormone (FSH; 50 ng/mL), folliculogenesis proceeded at a more rapid rate when compared to tissues treated with either agent alone [102]. After the addition of both melatonin (1 nM) and FSH, follicle size and ovum diameters were increased above those of other treatment groups after 7 days of incubation.…”
Section: Melatonin: Female Reproductive Healthmentioning
confidence: 99%
“…Although the information about the involvement of melatonin on preantral follicle development is limited, in a recent study, it was reported that melatonin in association with FSH promotes follicular growth of caprine preantral follicles [65]. Several studies also have described the effects of melatonin in antral follicles, such as regulation of sex steroid production, LH mRNA expression, Bcl2 and Casp3 production, and insulin-like growth factor and transforming growth factor beta activity [3,21,66].…”
Section: In the Folliclementioning
confidence: 99%